Editorial: Data-Driven Campaigning in a Comparative Context—Toward a 4th Era of Political Communication? - Luke, Stephanie (2024)
Contemporary political campaigning takes place both online and offline, and can be data-driven. In this piece, we review existing knowledge around data-driven campaigning (DDC) and introduce the new contributions made by the pieces within this thematic issue. We reveal how the studies included in this thematic issue of Media and Communication contribute to this existing knowledge by providing an up-to-date account of how DDC in general, and political microtargeting in specific, have been employed in election campaigns between 2021 and 2023, in a range of countries: France, Germany, the Netherlands, Sweden, and the US. As a collection, these studies highlight the variance that exists in the degree to which DDC is practiced, the range of DDC tools used, and attitudes toward DDC. In recent election campaigns, DDC takes many forms, and disapproval of DDC varies depending on how it is implemented.